2012
DOI: 10.1371/journal.pone.0047883
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight, Obesity, and Abdominal Obesity in a Representative Sample of Portuguese Adults

Abstract: This study determined the prevalence of overweight, obesity, and abdominal obesity in the Portuguese adults and examined the relationship between above mentioned prevalences and educational level. Body mass, stature, and waist circumference were measured in a representative sample of the Portuguese population aged 18–103 years (n = 9,447; 18–64 years: n = 6,908; ≥65 years: n = 2,539). Overweight and obesity corresponded to a body mass index ranging between 25–29.9 kg/m2 and ≥30 kg/m2, respectively. Abdominal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
3
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 28 publications
3
43
3
8
Order By: Relevance
“…Data in the present study showed that the prevalence of overweight and obesity was 34.2% and 12.7% in women, and 52.1% and 12.7% in men, respectively. Although our findings were self-reported, the prevalence of overweight and obesity among Spaniards is higher than the average values obtained by self-report in European countries (overweight: 25.6% in women and 36.6% in men; obesity: 10.1% in women and 9% in men) 23 and the Portuguese population 24 . The higher prevalence of overweight/obese men compared with women is consistent with previous findings in the USA and Europe 5,25 , suggesting the need for tailored strategies aimed at obesity reduction and physical activity promotion.…”
Section: Discussioncontrasting
confidence: 92%
“…Data in the present study showed that the prevalence of overweight and obesity was 34.2% and 12.7% in women, and 52.1% and 12.7% in men, respectively. Although our findings were self-reported, the prevalence of overweight and obesity among Spaniards is higher than the average values obtained by self-report in European countries (overweight: 25.6% in women and 36.6% in men; obesity: 10.1% in women and 9% in men) 23 and the Portuguese population 24 . The higher prevalence of overweight/obese men compared with women is consistent with previous findings in the USA and Europe 5,25 , suggesting the need for tailored strategies aimed at obesity reduction and physical activity promotion.…”
Section: Discussioncontrasting
confidence: 92%
“…1 Os últimos dados de prevalência publicados em Portugal indicam que cerca de 67% dos homens e 58% das mulheres adultas portuguesas têm excesso de peso ou obesidade (Índice de Massa Corporal (IMC) ≥ 25 kg/m 2 ). 2 Na etiologia desta patologia estão, não só a predisposição genética mas também mudanças sociais, económicas, culturais e físicas do meio ambiente. 1 Está bem descrito na literatura que a obesidade aumenta o risco de diversas doenças crónicas e as guidelines internacionais para a gestão do peso em adultos indicam que alterações do estilo de vida que conduzam à manutenção de 3-5% do peso perdido acarretam melhorias substanciais nos factores de risco para estas doenças.…”
Section: Introductionunclassified
“…These types of exercises are not appropriate for health gains in terms of weight, blood pressure, body fat, and waist circumference [10,21,22]. As expected, there were no significant differences in weight, blood pressure, body fat, and waist circumference across groups.…”
Section: Table 2 (Continued)mentioning
confidence: 63%